Computed tomographic colonography for colorectal cancer screening: Risk factors for the detection of advanced neoplasia. Issue 14 (10th June 2013) - Hassan, Cesare; Pooler, B. Dustin; Kim, David H.; Rinaldi, Antonio; Repici, Alessandro; Pickhardt, Perry J.
Abstract : BACKGROUND: The objective of this study was to determine whether age, sex, a positive family history of colorectal cancer, and body mass index (BMI) are important predictors of advanced neoplasia in the setting of screening computed tomographic colonography (CTC). METHODS: Consecutive patients who were referred for first‐time screening CTC from 2004 to 2011 at a single medical center were enrolled. Results at pathology were recorded for all patients who underwent polypectomy. Logistic regression was used to identify significant predictor variables for advanced neoplasia (any adenoma ≥10 mm or with villous component, high‐grade dysplasia, or adenocarcinoma). Odds ratios (ORs) were used to express associations between the study variables (age, sex, BMI, and a positive family history of colorectal cancer) and advanced neoplasia. RESULTS: In total, 7620 patients underwent CTC screening. Of these, 276 patients (3.6%; 95% confidence interval [CI], 3.2%‐4.1%) ultimately were diagnosed with advanced neoplasia. At multivariate analysis, age (mean OR per 10‐year increase, 1.8; 95% CI, 1.6‐2.0) and being a man (OR, 1.7; 95% CI, 1.3‐2.2) were independent predictors of advanced neoplasia, whereas BMI and a positive family history of colorectal cancer were not. The number needed to screen to detect 1 case of advanced neoplasia varied from 51 among women aged ≤55 years to 10 among men aged >65 years. The number of post‐CTC colonoscopies needed to detect 1 case of advanced neoplasia varied from 2 to 4. CONCLUSIONS: Age and sex were identified as important independent predictors of advanced neoplasia risk in individuals undergoing screening CTC, whereas BMI and a positive family history of colorectal cancer were not. These results have implications for appropriate patient selection. Cancer 2013;119:2549–2554 . © 2013 American Cancer Society . Abstract : When stratifying a large computed tomographic colonography (CTC) screening cohort according to age and sex, the number of individuals who would have to undergo CTC screening to detect 1 advanced neoplasm ranges from 51 among women aged <55 years to 10 among men aged >65 years. The possibility of stratifying the population undergoing CTC screening according to the risk of advanced neoplasia may prompt the development of more efficient risk‐reduction strategies.